Low Energy Intake Impairs Glucose Regulation and Stamina in Japanese Young Women - Kaneko Michiyo; Kaneko Takehiko; Otsuki Makoto (International Journal of Nutrition, 2016)
Energy intake has been decreasing these ten years in Japan, and low energy intake is remarkable especially among young women. We attempted to show the dietary habits and physiological function including glucose tolerance and stamina for endurance-running in contemporary young Japanese women who take insufficient energy. 85 healthy women aged 20.5±1.1 years were enrolled in the present study. Subjects were categorized in two groups; Group I (n=70) with higher energy intake, and Group II (n=15) with lower energy intake than the basal metabolic rate (BMR). Actual energy intake in Group I was 1598.8±282.1 kcal/day, and it was 1019.9±127.1 kcal/day in Group II (p<0.01). Standard 75-g oral glucose-tolerance test was performed, and the capillary glucose value was measured at the fingertip. In Group I, glucose values at fasting, 30, 60 and 120 min were 75.0±9.1, 132.1±25.2, 120.5±27.4, 105.3±19.5 mg/dl, and those in Group II were 78.9±7.7, 155.8±26.6, 142.2±26.6, 112.3±16.0 mg/dl, respectively. The values of Group II at 30 and 60 min showed significantly high (p< 0.01). Stamina and the intake of protein in Group II were significantly lower than those in Group I (p<0.05), and muscle mass and grip strength were less in Group II than in Group I, though there was no significant difference. We indicated with these results that low skeletal muscle was considered to be responsible for the impairment of glucose regulation in Group II. This study showed that young women with low energy intake should take sufficient energy and build skeletal muscle to prevent the impairment of glucose regulation.
Keywords: low energy intake